2015
DOI: 10.3354/meps11435
|View full text |Cite
|
Sign up to set email alerts
|

High ammonium availability amplifies the adverse effect of low salinity on eelgrass Zostera marina

Abstract: Climate change intensifies the frequency and intensity of rainfall events, which increases the discharge of freshwater and nutrients to coastal areas. This may lower salinity and increase nutrient availability and, thus, affect estuarine eelgrass populations. We studied the interactive effect of increasing NH 4 + levels and low salinity on estuarine eelgrass Zostera marina, grown in microcosm at various combinations of NH 4 + enrichment (0, 10 and 25 μM) and salinity (5, 12.5 and 20). Increasing NH 4 + had a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…oceanica , a species considered to be persistent, thus leading to the conclusion that the future impact of warming could be much worse for plants subject to high ammonium loading than for plants living in relatively pristine environments. These findings are consistent with a large number of studies, which have also reported synergistic effects between two simultaneous stressors on seagrasses [39,52,55,107]. However, most of these studies have focused on colonizing and opportunistic seagrass species; further studies are therefore required to shed light on the response of this, and other, persistent seagrass species to simultaneous exposure to two or more stressors.…”
Section: Discussionsupporting
confidence: 88%
“…oceanica , a species considered to be persistent, thus leading to the conclusion that the future impact of warming could be much worse for plants subject to high ammonium loading than for plants living in relatively pristine environments. These findings are consistent with a large number of studies, which have also reported synergistic effects between two simultaneous stressors on seagrasses [39,52,55,107]. However, most of these studies have focused on colonizing and opportunistic seagrass species; further studies are therefore required to shed light on the response of this, and other, persistent seagrass species to simultaneous exposure to two or more stressors.…”
Section: Discussionsupporting
confidence: 88%
“…Prolonged exposure to excess NH4+ is toxic to plants although the underlying mechanisms remain partly unresolved (Britto et al ). Plants exposed to high NH4+ levels accumulate intra‐cellular NH4+, obtain lower pigment concentrations, higher levels of oxidative damages, and impaired photosynthesis and growth (e.g., Brun et al ; Villazán et al ; Zhou et al ). Various processes may serve to reduce high concentrations of NH4+ in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…The response of seagrasses to multiple stressors has lately been addressed experimentally in a number of two‐factor studies where potential interactions between a variety of factors have been addressed (Hootsmans et al ; Kahn and Durako ; Koch et al ; de los Santos et al ; Collier et al ; Höffle et al ; Holmer et al ; La Nafie et al ; Jiang et al ; Villazán et al ; York et al ; Salo and Pedersen ; Castorani et al ; Villazán et al ; Hasler‐Sheetal et al ; Moreno‐Marín et al ). The conclusions in many of these articles infer a prevalence of synergistic effects in seagrasses when exposed to multiple stressors, although this has rarely been tested explicitly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, experiments assessing the interactions between temperature and nutrients are rare due to experimental and budgetary constraints. Some studies on seagrasses demonstrated that synergistic interactions occur when plants are exposed to a combination of stressors, such as osmotic, light, temperature and eutrophication (Touchette and Burkholder, 2000;Collier et al, 2011;Villazán et al, 2013Villazán et al, , 2015Ontoria et al, 2019b). However, the responses were highly specific for the species assessed and varied according to the life stage of the plant.…”
Section: Introductionmentioning
confidence: 99%